2021
DOI: 10.3390/e23040398
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Information-Theoretic Detection of Dynamical Organization in Complex Systems

Abstract: The identification of emergent structures in complex dynamical systems is a formidable challenge. We propose a computationally efficient methodology to address such a challenge, based on modeling the state of the system as a set of random variables. Specifically, we present a sieving algorithm to navigate the huge space of all subsets of variables and compare them in terms of a simple index that can be computed without resorting to simulations. We obtain such a simple index by studying the asymptotic distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…The whole method (choice of an index based on entropic observations, its normalization, application of the iterated sieving algorithm-possibly by using at each stage only groups of relatively small size-until the final groups cannot be further expanded) is called here "full RI method" where RI stands for "Relevance Index" (in [21] we present several indices that can be used within the RI method, and we evaluate their effects and advantages). An example of application of the RI method is presented in Appendix D. For the sake of simplicity, in the following we will refer to the algorithm that implements this method, using the zI index, as the "full zI algorithm" (a version of the software, developed in Python language, is available at the link: https://github.com/gianlucadaddese/Iterative-zI, accessed on 23 April 2021).…”
Section: The Full Ri Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The whole method (choice of an index based on entropic observations, its normalization, application of the iterated sieving algorithm-possibly by using at each stage only groups of relatively small size-until the final groups cannot be further expanded) is called here "full RI method" where RI stands for "Relevance Index" (in [21] we present several indices that can be used within the RI method, and we evaluate their effects and advantages). An example of application of the RI method is presented in Appendix D. For the sake of simplicity, in the following we will refer to the algorithm that implements this method, using the zI index, as the "full zI algorithm" (a version of the software, developed in Python language, is available at the link: https://github.com/gianlucadaddese/Iterative-zI, accessed on 23 April 2021).…”
Section: The Full Ri Methodsmentioning
confidence: 99%
“…The knowledge of the theoretical distribution of the integration values of such a system would, however, allow to avoid this load. In [21] it was shown that the quantity 2mI (m being the number of observations) follows a Chi Square distribution, whose freedom degrees are a function of the number of variables of the subset and on the cardinality of their alphabet.…”
Section: The Zi Indexmentioning
confidence: 99%
See 3 more Smart Citations